Research on teaching and learning with the literacies of young adolescents - Malu, Kathleen F.; Schaefer, Mary Beth (Handbook of research in middle level education series ;, 2015)
Research on middle level education indicates that student learning at the middle level has a deep and abiding influence on post-secondary opportunities and career paths. As research continues to highlight the urgency of engaging middle level students in academic learning, it is increasingly clear that these students' multiple literacies must become a part of teaching and learning. Understanding how to infuse the literacies of middle level students across classroom activities is a critical part of improving student achievement.This volume in The Handbook series shares literacy research from multiple contexts and deepens our understanding of the literacies that middle level students use in and out of school. This volume includes research that identifies how to best teach and learn with our increasingly diverse students. The perspectives that emerge from this volume help us examine the current state of new and evolving literacies and construct a cutting edge research agenda for middle level literacy education. Research reports focus on digital literacies including social networking media and games, English language learners, high stakes literacy tests and middle level learners, specifically boys, and literacy teaching and learning in middle level teacher education programs. A wide range of research methods and modes are used in these reports including case studies, teacher research, narrative inquiry, survey research, and action research.